2012
DOI: 10.1186/1749-8090-7-35
|View full text |Cite
|
Sign up to set email alerts
|

Chest trauma experience over eleven-year period at al-mouassat university teaching hospital-Damascus: a retrospective review of 888 cases

Abstract: BackgroundThoracic trauma is one of the leading causes of morbidity and mortality in developing countries. In this study, we present our 11-year experience in the management and clinical outcome of 888 chest trauma cases as a result of blunt and penetrating injuries in our university hospital in Damascus, Syria.MethodsWe reviewed files of 888 consequent cases of chest trauma between January 2000 and January 2011. The mean age of our patients was 31 ± 17 years mostly males with blunt injuries. Patients were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 16 publications
8
41
1
4
Order By: Relevance
“…These incidences are consistent with reports suggesting a 10–15% incidence of chest injuries among trauma patients [12], [13]. At the same time, most chest injuries in our patients were minor or moderate and resolved after conservative treatment, as reported in other major earthquakes [2], [3], [14].…”
Section: Discussionsupporting
confidence: 93%
“…These incidences are consistent with reports suggesting a 10–15% incidence of chest injuries among trauma patients [12], [13]. At the same time, most chest injuries in our patients were minor or moderate and resolved after conservative treatment, as reported in other major earthquakes [2], [3], [14].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that thoracic trauma cases with accompanying head trauma had greater mortality rates than those without it. [24,25] In this study, only 30 (5.6%) cases had isolated thoracic trauma. Of the patients in this study with accompanying traumas, only those with accompanying CNS trauma had significantly higher mortality rates.…”
Section: Discussionmentioning
confidence: 55%
“…Most rib fracture cases (69%) are associated with other thoracic injuries mainly hemo/pneumothorax and lung contusion, 5% of which diagnosed after 24 hours of trauma (15). In our study, a chest tube was inserted in 70.7%, mostly due to pneumothorax, hemothorax, or hemopneumothorax.…”
Section: Discussionmentioning
confidence: 58%